Is there an association between fertility and domestic violence in Nepal?AJOG MFM at a Glance - Sarah Raifman, MSc; Mahesh Puri, PhD; Jennet Arcara, PhD; Nadia Diamond-Smith, PhD (Elsevier, 2021)
BACKGROUND: Intimate partner violence and nonpartner violence are common in Nepal, yet the relationship between violence and fertility is unclear. The risk of violence for young, newly married women in Nepal may be associated with becoming pregnant and giving birth due to either the family's desire to protect the fetus (reducing violence) or the added household stressors that accompany a pregnancy (increasing violence). OBJECTIVE: This study aimed to investigate changes in partner and nonpartner violence over time in early marriage and explore the hypothesis that conception and childbirth may be associated with risk of domestic violence. STUDY DESIGN: We surveyed newly married women aged 18 to 25 years and living in the Nawalparasi district of Nepal in 4 rounds of data collection at 6-month intervals over 2 years. At each survey, interviewers asked whether participants had experienced any violence within the previous 6 months, including details about the type and perpetrator of the violence, and whether they had ever been pregnant or given birth. RESULTS: A cohort of 200 participants completed the baseline survey and 183 (92%) completed all 4 survey rounds. The proportion of participants experiencing any recent violence increased substantially over time. By the end of the study, 58% of participants reported experiencing intimate partner violence, nonpartner violence, or both in the previous 6 months. Most participants had been pregnant (148 [79%]) and given birth (117 [64%]) during the study period. Multivariate models were used to estimate the odds of any intimate partner violence during the previous 6 months. The odds of experiencing any intimate partner violence were more than 2 times higher for participants who became pregnant (odds ratio, 2.2; 95% confidence interval, 1.0-4.7) and gave birth (odds ratio, 2.9; 95% confidence interval, 1.2-7.2) than for those who did not. After adjusting for covariates, pregnancy and birth were not statistically associated with a change in the odds of reporting any nonpartner violence. CONCLUSION: Our study indicates that newly married young women in Nepal are vulnerable to violence in the home from both partners and nonpartners. Our findings support the hypothesis that risk of intimate partner violence may be greater during the perinatal period. The longitudinal nature of the study contributes to the existing literature by adding evidence that violence increases in early marriage and is positively associated with pregnancy and birth.